Adverse Pregnancy Outcomes in Women with Sickle Cell Trait - Wellenstein, Whitney L.; Sullivan, Shannon; Darbinian, Jeanne; Ritterman Weintraub, Miranda L.; Greenberg, Mara (American Journal of Perinatology Reports, 2019)
Objective To compare adverse pregnancy outcomes between women with sickle cell trait (SCT) and women with normal hemoglobin.Study Design A retrospective cohort study of women who delivered within Kaiser Permanente Northern California between 2006 and 2013. Using hemoglobin electrophoretic profiles, we defined women with hemoglobin AS (HbAS) as having SCT and those with hemoglobin AA (HbAA) as having normal hemoglobin. Outcomes were pregnancy-induced hypertension (PIH), small for gestational age (SGA), gestational diabetes (GDM), and preterm delivery (PTD). Demographic and pregnancy outcome variations were assessed in bivariate analyses. Multivariable logistic regression modeling was used to estimate odds ratios for the association between primary outcomes and selected characteristics.Results Of 31,840 eligible women, 868 (2.7%) had SCT. Women with SCT were more likely to have PIH (15.6% vs. 12.2%, p value = 0.003) and SGA (8.3% vs. 6.1%, p value = 0.008), less likely to have GDM (6.8% vs. 9.8%, p value = 0.003) and had similar PTD prevalence (8.1% vs. 7.6%, p value = 0.600). In multivariable analyses, SCT was not an independent predictor of these outcomes. Racial/ethnic minorities had higher adjusted odds of PIH, SGA, and GDM.Conclusion SCT alone does not appear to be associated with adverse pregnancy outcomes. Race/ethnicity is a risk factor for adverse pregnancy outcomes.
Keywords: adverse pregnancy outcomes in African American women; hemoglobinopathy in pregnancy; sickle cell trait